Proceedings of the 9th Workshop on Computational Approaches to Subjectivity, Sentiment and Social Media Analysis 2018
DOI: 10.18653/v1/w18-6204
|View full text |Cite
|
Sign up to set email alerts
|

Language Independent Sentiment Analysis with Sentiment-Specific Word Embeddings

Abstract: Data annotation is a critical step to train a text model but it is tedious, expensive and time-consuming. We present a language independent method to train a sentiment polarity model with limited amount of manuallylabeled data. Word embeddings such as Word2Vec are efficient at incorporating semantic and syntactic properties of words, yielding good results for document classification. However, these embeddings might map words with opposite polarities, to vectors close to each other. We train Sentiment Specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It is therefore hardly surprising that most efforts have focused on the application of machine learning algorithms, which produce classifiers whose statistical model is learnt, typically, in a supervised fashion from a corpus of labeled examples, such as user reviews (Pang et al 2002;Turney 2002) or tweets (Nakov 2016). The techniques to improve performance of classifiers have progressively gained computational complexity over the years; at present, supervised methods such as Support Vector Machine (SVM), Bayesian Networks and Neural Networks, among others are commonplace, as are unsupervised learning techniques based on pre-trained word embeddings (such as Word2vec) or clustering techniques, e.g., Tang et al 2014;Kalchbrenner et al 2014;Kim 2014;Fu et al 2018;Saroufim et al 2018), with or without the aid of external lexical resources (sentiment dictionaries).…”
Section: Related Workmentioning
confidence: 99%
“…It is therefore hardly surprising that most efforts have focused on the application of machine learning algorithms, which produce classifiers whose statistical model is learnt, typically, in a supervised fashion from a corpus of labeled examples, such as user reviews (Pang et al 2002;Turney 2002) or tweets (Nakov 2016). The techniques to improve performance of classifiers have progressively gained computational complexity over the years; at present, supervised methods such as Support Vector Machine (SVM), Bayesian Networks and Neural Networks, among others are commonplace, as are unsupervised learning techniques based on pre-trained word embeddings (such as Word2vec) or clustering techniques, e.g., Tang et al 2014;Kalchbrenner et al 2014;Kim 2014;Fu et al 2018;Saroufim et al 2018), with or without the aid of external lexical resources (sentiment dictionaries).…”
Section: Related Workmentioning
confidence: 99%
“…In [13], the authors suggested rating tweets in French using a dataset of positive and negative emojis and training them to include Sentiment Specific Word Embeddings (SSWE) on top of an unsupervised Word2Vec model. It updated the embedding through deep learning with bidirectional LSTM on the auto-labeled data.…”
Section: Related Workmentioning
confidence: 99%
“…Another issue with pre-trained embedding is that it does not account for sentiment polarity of words and might map words with opposite polarities to vectors closer to each other in Euclidean space. A novel sentiment-specific word embedding is proposed for language-independent sentiment analysis, which shows an improvement over traditional pre-trained embeddings of word2vec [12].…”
Section: Related Workmentioning
confidence: 99%